The Impact of Psychological Contract Breach on Student-Athlete Perceived In-Role Performance and Organizational Citizenship Behaviors - Christopher R. Barnhill; Brian A. Turner (Journal of Applied Sports Management, 2015)
Recent research has demonstrated that breached psychological contracts between student-athletes and their coaches can have negative consequences for team members (Barnhill, Czekanski, & Turner, 2013; Barnhill & Turner, 2013, 2014). While these studies are informative, they have been focused on student-athlete attitudes. The purpose of this study was to explore how psychological contracts affect student-athletes' behaviors and performance. The results indicated that neither psychological contract breaches, nor psychological contract violation are significantly related to organizational citizenship behaviors or in-role performance of studentathletes. Implications and suggestions for future results are discussed.
Keywords: coach-athlete relationship; psychological contracts; student-athletes; perceived performance; organizational citizenship behaviors